(untitled) (Training and Practice : Journal of Educational Sciences, 2019)
When different cultures meet it is usually the members of the other group that are considered rude because they do not behave in a way the first group would expect its own members to behave. Because the strangers’ behaviour is strange and not in accordance with local expectations, it cannot be prognosticated what they are up to, so the locals will grow reserved and suspicious with the strangers. It is undoubted that tensions experienced more and more often in culturally and ethnically increasingly diverse societies of the 21st century pose a great responsibility to educational science. Luckily educational science can effectively contribute towards a peaceful coexistence of rather different cultures. Besides imparting an empathic knowledge of one’s own and the other culture’s traditions it can establish a concept of humankind that recognises the fellow human, even despite different values and habits, and even if their ideology or behaviour appears strange to us.